Strategic information management (SIM) among managers in Malaysian business environment - Hussin, Norhayati (2017)
Strategic Information Management (SIM) in an organization is sustained by significant factors. Without these factors, SIM ceased to exist, and therefore organization could not capitalize on the flexibility of information resources to develop innovative strategies to face the competitive environment. Not understanding what factors could contribute to SIM in an organizational context, many organizations have failed to capitalize their information resources strategically to assist them in their competition. With the fact that SIM is dependable on certain factors, it is only important that organization should determine, understand, and strategize the development of these factors. Strategic Information Management (SIM) occurs in an organization where managers utilize strategic information (SIU) with the purpose to formulate business strategies. To successfully use the strategic information, the managers must have a positive Information behaviour (IBM) with the support of Organizational Information Management Practices (OIMP) and Organizational Information Technology Practices (OITP) in an organization.